Tailoring Atomic Ordering Uniformity Enables Selectively Leached Nanoporous Pd‐Ni‐P Metallic Glass for Enhanced Glucose Sensing - Yu Lou; Jian Li; Zhongzheng Yao; Zhenduo Wu; Huiqiang Ying; Lan Tan; Sinan Liu; Jianrong Zeng; Ruohan Yu; Hong Liu; Xun‐Li Wang; He Zhu; et al. (Advanced Science)
Abstract Constructing nanostructures, such as nanopores, within metallic glasses (MGs) holds great promise for further unlocking their electrochemical capabilities. However, the MGs typically exhibit intrinsic atomic‐scale isotropy, posing a significant challenge in directly fabricating anisotropic nanostructures using conventional chemical synthesis. Herein a selective leaching approach, which focuses on tailoring the uniformity of atomic ordering, is introduced to achieve pore‐engineered Pd‐Ni‐P MG. This innovative approach significantly boosts the number of exposed active sites, thereby enhancing the electrochemical sensitivity for glucose detection. Electrochemical tests reveal that the nanoporous Pd‐Ni‐P MG exhibits high sensitivity (3.19 mA mm⁻¹ cm⁻2) and remarkable stability (97.7% current retention after 1000 cycles). During electrochemical cycling, synchrotron X‐ray pair distribution function and X‐ray absorption fine structure analyses reveal that the distance between active sites decreases, enhancing electron transport efficiency, while the medium‐range ordered structure of the Pd‐Ni‐P MG remains stable, contributing to its exceptional glucose sensing capabilities. A microglucose sensor is successfully developed by integrating the nanoporous Pd‐Ni‐P MG with a screen‐printed electrode, demonstrating the practical applicability. This study not only offers a new avenue for the design of highly active nanoporous MGs but also sheds light on the mechanisms behind the high electrochemistry performance of MGs.